A retrospective study of individualized endovascular treatment for symptomatic intracranial atherosclerotic stenosis in patients with ischemic stroke/transient ischemic attack - Mao, Lun-Lin; Ma, Ai-Jin; Liu, Zhi-Qing; Zhang, Jin; Xu, Yuan-Feng; Chen, Wen-Ya; Cao, Yong-Jun (Frontiers in Neurology, 2022)
Background: Endovascular treatment (EVT) is one of the effective treatment procedure for the symptomatic intracranial atherosclerotic stenosis (sICAS). Aim and methods: We evaluated the efficacy and safety of individualized endovascular treatment for sICAS patients. Clinical and imaging follow-ups were carried out to collect the data of 29 sICAS patients after 6 months of individualized endovascular treatment. Results and conclusions: 31 lesions of 29 sICAS patients received endovascular treatment. The median age was 61 years (IQR 54-69 years). The median preoperative stenosis was 90% (IQR 80-95%), and the mean stenosis length was (8.10 + 3.27) mm. The most commonly used surgical procedure was Balloon-Mounted Stent (BMS) in 19 cases (65.52%), Self-expanding Stent (SES) in 7 cases (24.14%), Balloon Dilation Angioplasty (BDA) in 3 cases (10.34%). The mean stenosis length in the SES group (11.86 + 1.46 mm) was greater than that in the BMS group (6.14 + 1.59 mm) (P < 0.001). The median stenosis was 90% (IQR 80-92.5%) in the BMS group, lower than 99% (IQR 95-100%) in the SES group (P < 0.001). The median postoperative residual stenosis was 20% (IQR 15-25%), significantly improved compared with preoperative (P < 0.001). The success rate of the surgical technique was 93.10% (27/29). One patient (3.45%) had IS recurrence within 48h after surgery, and the restenosis rate within 6 months after surgery was 6.90% (2/29). No patient died or had recurrent IS. Our data demonstrated that individualized endovascular treatment method could be potentially significant and safe for sICAS patients.